EFEK PEMBERIAN JUS BUAH PISANG AMBON (Musa paradisiaca var. sapientum (L.) Kunt.) TERHADAP KADAR GLUKOSA DARAH TIKUS JANTAN GALUR WISTAR YANG TERBEBANI GLUKOSA - Katherine Jessica Ariani; Yunita Linawati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
This research is to know the effect of giving Musa paradisiaca var. sapientum (L.) Kunt. juice to the blood glucose levels and to know the most effective of giving Musa paradisiaca var. sapientum (L.) Kunt. dose to lower the blood glucose levels in rats with oral glucose tolerance. This research was experimental study with one way-complete-random design using 25 male rats were divided into five groups. The rats in group I (negative control) were given of CMC 1%, the group II rats were given 0.64mg/kgBW doses of Glibenclamide (positive control), and group III,IV and V were given 5, 10 and 20 ml/kgBW doses of Musa paradisiaca var. sapientum (L.) Kunt. juice. The hypoglycemic effect of Musa paradisiaca var. sapientum (L.) Kunt. juice was tested by following the Oral Glucose Tolerance Test (OGTT) method. The blood-glucose contents were taken, at 0 minutes before OGTT, and also taken at minutes of 15, 20, 45, 60, 90, 120, 180, and 240 after OGTT, from the tested animal that had been gotten the pre-treatment of negative control, positive control and Musa paradisiaca var. sapientum (L.) Kunt. juice. The blood glucose levels was determined by using enzymatis GOD-PAP method. The AUC0-240 was statistically analyzed using one way ANOVA and Scheffe test with 95% convidence level. The result of this research showed that Musa paradisiaca var. sapientum (L.) Kunt. can lower on rats in burdened glucose. The effective dose of Musa paradisiaca var. sapientum (L.) Kunt. juice can lower glucose blood levels at 5ml/kgBW.